2011
DOI: 10.1161/strokeaha.110.601575
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency of Silent Pulmonary Embolism in Patients With Cryptogenic Stroke and Patent Foramen Ovale

Abstract: Background and Purpose-Deep vein thrombosis and pulmonary embolism (PE) prove venous embolic activity and enforce the suspicion of paradoxical embolism in patients with stroke with patent foramen ovale. Because it has implications in secondary prevention, we investigated the frequency of silent PE in such a cohort of patients. Methods-Patients with cryptogenic stroke or transient ischemic attack and patent foramen ovale who underwent a ventilation perfusion scintigraphy were identified from a stroke registry. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 8 publications
0
33
0
3
Order By: Relevance
“…Blinded from clinical data all scans were independently evaluated by two experts according to the PIOPED (prospective investigation of pulmonary embolism diagnosis) criteria modified for SPECT images, as described by Reinartz et al [5,9,10]. In scans graded differently a consensus read was undertaken.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blinded from clinical data all scans were independently evaluated by two experts according to the PIOPED (prospective investigation of pulmonary embolism diagnosis) criteria modified for SPECT images, as described by Reinartz et al [5,9,10]. In scans graded differently a consensus read was undertaken.…”
Section: Methodsmentioning
confidence: 99%
“…As a functional PFO closure was observed after treatment of acute massive pulmonary emboli, a fluctuation in pulmonary atrial pressure might be involved in the mechanism of shunt dynamic across a PFO [2-4]. Considering that silent pulmonary embolism (PE) is a frequent finding in patients with CS and PFO, it raises the question whether an increase in right atrial pressure due to silent pulmonary embolism may have a similar impact on the development of RLS dynamics [5]. We therefore investigated the relevance of silent PE in a cohort of PFO patients with CS with a re-assessment of RLS on follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of pulmonary embolism can persist for up to 4 weeks post stroke [67]. A review of a relatively small cohort of cryptogenic stroke patients found a significant incidence of silent pulmonary embolism (37%), but did not comment as to whether or not this led to a resultant hypoxic state [68]. Improvements in mechanical, pharmacological and therapy based regimes are the likely reason pulmonary embolism is now a relative rarity.…”
Section: Causes Of Hypoxia In Acute Strokementioning
confidence: 99%
“…In other studies including cryptogenic stroke and patent foramen ovale, PE was found in up 20% to 37% of patients, though the great majority of these cases were asymptomatic and only recognized by dedicated testing required by the research design. 2122 …”
Section: Discussionmentioning
confidence: 99%